Online Analytical Processing (OLAP) for Disaster Report - Budi Permana, Kadek Ary; Putri Wulandari, Dewa Ayu; Mertasana, Putu Arya (International Journal of Engineering and Emerging Technology, 2018)
Data analysis of disaster is very important for supporting in making decision to cope with the next disaster or prepare if the disaster will happen again. Online Analytical Processing (OLAP) becomes solution to get analysis by using certain analysis that supplied in OLAP. To supply the data analysis in which done by OLAP so the data as the representative in multidimensional model that manages the data in cube form. Warehouse data can be called as the place from source data that used to make easier in analysis information process in it because concept of data dimensional offered. The planning data warehouse is basically by source data that gotten and decided by the description of needs from the users. OLAP in this disaster report success in implementation with helping data warehouse and imply snowflake schema to dimensional data first.